Early Impact of the COVID-19 Pandemic on Acute Stroke Treatment Delays. (23rd January 2021) - Neves Briard, Joel; Ducroux, Célina; Jacquin, Grégory; Alesefir, Walid; Boisseau, William; Daneault, Nicole; Deschaintre, Yan; Eneling, Johanna; Gioia, Laura C.; Iancu, Dana; Odier, Céline; Raymond, Jean; et al.
ABSTRACT: This is an observational cohort study comparing 156 patients evaluated for acute stroke between March 30 and May 31, 2020 at a comprehensive stroke center with 138 patients evaluated during the corresponding time period in 2019. During the pandemic, the proportion of COVID-19 positive patients was low (3%), the time from symptom onset to hospital presentation was significantly longer, and a smaller proportion of patients underwent reperfusion therapy. Among patients directly evaluated at our institution, door-to-needle and door-to-recanalization metrics were significantly longer. Our findings support concerns that the current pandemic may have a negative impact on the management of acute stroke.